Pre-Service Teachers’ Experiences and Challenges in Creating Digital Learning Media Concerning TPACK Framework - Widihastutik, Amelia; Dewi Saraswati, Girindra Putri; Wahyuni, Sri (Universitas Negeri Semarang, 2025)
Implementing Information and Communication Technology (ICT) in education transforms traditional learning into modern learning. Teachers must adapt to technology in this era, especially in creating digital learning media. Before becoming formal teachers, they join teacher training programs as pre-service teachers. They develop and implement digital learning media in real teaching. Based on the literature gap, it aims to describe the experiences and challenges overcome by pre-service teachers in developing digital learning media through the TPACK Framework. This study used qualitative descriptive research. The participant of this study was 32 English pre-service teachers were attending the teacher training program namely UNNES LANTIP 4 Program. The data were derived from the closed-ended questionnaire and semi-structured interview. Thematic analysis and method triangulation were employed to analyze the data. The results revealed that all the pre-service teachers perceived mastering content, pedagogical, and technological knowledge. They perceived great experiences in developing digital learning media concerning four aspects of TPACK framework: Technological Content Knowledge (TCK), Technological Pedagogical Knowledge (TPK), Technological Knowledge (TK), and Technological Pedagogical Content Knowledge (TPACK). In addition, they also perceived several challenges in developing digital learning media through the TPACK framework. For instance, time constraints in teaching technology, insufficient training programs, time constraints in developing digital learning media, limited access and resources, technical problems, and technology misuse. By understanding this study, pre-service teachers could develop appropriate digital learning media concerning TPACK Framework.